A Qualitative Study of Occupational Therapists’ Understanding of Spirituality in South Africa - Balbadhur, Raashmi (Journal of religion and health, 2023)
Occupational therapy is a holistic profession that assists clients to restore meaning to their lives—a vital spiritual task. Spirituality is a multifaceted and multidimensional construct that occupational therapists need to integrate into everyday practice. In this study, Occupational Therapy educators’ and clinicians’ understanding of spirituality in their practice was qualitatively explored by purposively selecting 24 participants who attended a workshop based on an appreciative approach, in Gauteng, South Africa. Data were collected through self-report interview schedules and focus group inquiries and were analysed using the creative hermeneutic method. Participants expressed spirituality in occupational therapy as connectedness, meaning of life and client-centred practice.